Pengembangan Profesionalisme Guru Melalui Model Lesson Study - Rudi Prihantoro (Jurnal Pendidikan dan Kebudayaan, 2011)
Lesson study (LS) is a competence development process in a systematic teacher professionalism which aims to make learning better and more effective. Stages LS ie Plan, Do, See. LS requires the stability of education policy, curriculum, flexible, self-reflection and cultural cooperation. Excess LS is oriented to students, working as a team, developing a teaching technique. LS development in the professionalism of teachers is to plan learning objectives and subject matter, review and develop learning; deepen knowledge that is taught; thinking about long-term goals of students; designing collaborative learning; examines the process of learning, behavior and student learning outcomes, and, develop pedagogical. LS carried out by forming groups of LS, LS focus, Planning the Research Lesson (RL), RL teach and observe, discuss and analyze the RL, as well as reflect and plan for re-LS. LS Benefits include triggering the emergence of self-motivation to develop, train educators to â€œseeâ€ the learner, making research an integral part of education, dissemination of innovation and new approaches, puts educators in a respectable position.ABSTRAKLesson study(LS) adalah sebuah proses pengembangan kompetensi keprofesionalan guru secara sistematis Â yang Â bertujuan Â untuk Â menjadikan proses Â pembelajaran Â lebih Â baik Â dan Â efektif. Â Tahapan Â LS yaitu Plan, Do, See. S mensyaratkan stabilitas kebijakan pendidikan, kurikulum fleksibel, budaya refleksi diri dan kerjasama. Kelebihan LS adalah berorientasi pada siswa, bekerja sebagai tim, mengembangkan teknik mengajar. Pengembangan LS dalam profesionalime guru yaitu merencanakan tujuan pembelajaran dan Â materi pokok; mengkaji Â dan Â mengembangkan Â pembelajaran; Â memperdalam Â penge-tahuan yang diajarkan; Â memikirkan Â tujuan Â jangka Â panjang Â siswa; Â merancang pembelajaran Â kolaboratif; Â mengkaji proses belajar, perilaku dan hasil belajar siswa; dan, mengembangkan pedagogis. LS dilaksanakandengan membentuk kelompok LS, memfokuskan LS, Merencanakan Research Lesson(RL), membelajarkan dan mengamati Â RL, Â mendiskusikan Â dan Â menganalisis Â RL, serta Â merefleksikan Â dan Â merencanakan Â kembali LS. Manfaat LS diantaranya memicu munculnya motivasi untuk mengembangkan diri, melatih pendidik â€œmelihatâ€ peserta didik, menjadikan penelitian sebagai bagian integral pendidikan, penyebaran inovasi dan pendekatan baru, menempatkan para pendidik pada posisi terhormat.